MOBILITAS SOSIAL PETANI PERKEBUN DESA BUKIT LINGKAR DI KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Fitroh Hidayati; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study is to research how the Social Mobility Farmers estate that existed in the Bukit Lingkar village of Hiil Circle is the Districh of Batang Cenaku indragiri districh upstream. Devalopment and construction of this land will craate a variety of economic activites that can be done by the community, in addition to creating nem jobs and open again for the public. With the farmer’s estates can we know the negative impacts and positive impacts. And there is a from of social mobility, factors affecting social mobility. The data tekhnic collection with the questioner, interview and documentation. And the analisys of data is descriptive analysis of quantitative where the data presented in the form of a diagrams, percentages, images, and descriptions. The results snow that social mobility farmers etates that should raise welfare in public life, but on the contrary that it does not happen they get welfare. And poverty can limit the opportunity for someone to develop and achieve certain social status. It is addressing that poverty in the village of Round Hill very minimum. But there are from of social mobility social namely social mobility horizontal and social mobility vartikal. Both from are respectively a process of social mobility. A person or group of people who perfoem economic activities by utilizing natural resources. Investment io oil palm plantations will be long-term. Do not let social interests can not be in the case of government, especially regarding land issues. This could lead to a conflict-konflik in the village of Bukit Lingkar.Keyword: Social Mobility, farmer, estate.